Non‐alcoholic fatty liver disease from pathogenesis to management: an update - Giovanni Musso; Roberto Gambino; Maurizio Cassader (2009)
Summary Non‐alcoholic fatty liver disease (NAFLD), the most common chronic liver disease in the Western world, is tightly associated with obesity and metabolic syndrome. NAFLD entails an increased cardiometabolic and liver‐related risk, the latter regarding almost exclusively non‐alcoholic steatohepatitis (NASH), the progressive form of NAFLD. Pathogenetic models encompass altered hepatic lipid partitioning and adipokine action, increased oxidative stress, free fatty acid lipotoxicity. On this basis, lifestyle‐, drug‐ or surgically induced weight loss, insulin sensitizers, antioxidants, lipid‐lowering drugs have been evaluated in NAFLD/NASH. Most trials are small, of short duration, nonrandomized, without histological end points, thus limiting assessment of long‐term safety and efficacy of proposed treatments. All NAFLD patients should be evaluated for their metabolic, cardiovascular and liver‐related risk. Liver biopsy remains the gold standard for staging NAFLD, but non‐invasive methods are under intense development. Weight loss through lifestyle intervention is the initial approach, because of established efficacy on NAFLD‐associated cardiometabolic abnormalities, and to emerging benefits on necroinflammation and overall disease activity in NASH. Bariatric surgery warrants further evaluation before it can be routinely considered in morbidly obese NASH. Larger‐ and longer‐duration randomized trials assessing safety and benefits of drugs on patient‐oriented outcomes are needed before pharmacological treatment can be routinely recommended for NASH.